On Types of - Functions (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2018)
In  this  paper  we  introduce  and study another  types  of   functions   in a topological spaces  namely , -compact and  -coercive by  using  the concept  of  -open sets . Also we investigate some properties of these concepts and the relation between them.